LIQUEFACTION ASSESSMENT BASED ON GRAIN SIZE AND CPT ANALYSIS FOR BIROBULI AREA, SOUTH PALU - Siti Nurlita Fitri; I Made Wahyu Pramana (TEKNISIA, 2022)
Birobuli is located in South Palu, which has highly vulnerable to earthquakes. One of the phenomena that usually occur after an earthquake is liquefaction which causes significant damage and loss of life. Furthermore, all the infrastructure is required to analyze the effect of external load and potential hazards. This research aims to investigate the liquefaction potential in Birobuli, South Palu. The method was divided into two categories: grain size distribution analysis and empirical formula based on CPT data. The result presented a similar trend in grain size analysis which consist of all the range in the potential to liquefaction, while the CPT result describes the same meaning. The CPT 1 result showed SF<1 between 0-5m and 9-11m, while CPT 2 had fluctuating data in ranges between 0.18-2.00 in 0-4m, SF under 2 in 6-8m and 9-11m. This study was expected to provide information for local government as disaster mitigation for Birobuli Area.